Development of Biocompatible and Functional Polymeric Nanoparticles for Site-Specific Delivery of Radionuclides - Lepareur, Nicolas; Leal E Costa, Loleh; Bocqué, Maëva; Blondelle, Clément; Ruello, Clément; Desjulets, Marie; Noiret, Nicolas; Cammas-Marion, Sandrine (Frontiers in Medicine, 2015)
Introduction: Encapsulation of biologically active molecules into nanoparticles (NPs), for sitespecific delivery, is a fast growing area. These NPs must be biocompatible, non-toxic, and ableto release their load in a controlled way. We have developed a series of NPs based on (bio)degradable and biocompatible poly(malic acid) derivatives, poly(benzyl malate) (PMLABe), with its PEG-grafted stealth analogue and target-specific biotin-PEG-b-PMLABe one. A lipophilic radiotracer has then been encapsulated into these NPs. Methods: Monomers were synthesized from DL-aspartic acid. PEG42-b-PMLABe73 and Biot-PEG66-b-PMLABe73 block copolymers were obtained by anionic ring-opening polymerization of benzyl malolactonate in presence of -methoxy--carboxy-PEG42 and -biotin--carboxy-PEG66 as initiators. NPs were prepared by nanoprecipitation. Size, polydispersity and zeta potential were measured by DLS and zetametry. 99mTc-SSS was prepared as previously described. Encapsulation efficacy was assessed varying different parameters, such as encapsulation with preformed NPs or during their formation, influence of the solvent, and of the method to prepare the NPs. After decay, 99mTc-loaded NPs were also analyzed by DLS and zetametry. NPs’ morphology was assessed by TEM. Results: 99mTc-SSS was added during nanoprecipitation, using two different methods, to ensure good encapsulation. Radiolabeled NPs present increased diameters, with identical low polydispersity indexes and negative zeta potentials in comparison to non-radiolabeled NPs. Conclusion: A radiotracer was successfully encapsulated, but some further optimization are still needed. Next step will be to modify these radiolabeled NPs with an hepatotrope peptide, and to replace 99mTc with 188Re for therapy. Our team is also working on drugs’ encapsulation and grafting of a fluorescent probe. Combining these modalities is of interest for combined chemo-/radiotherapy, bimodal imaging and/or theranostic approach.